Investigating UX work in Software Startups: A Survey about Attitudes, Methods, and Key Challenges - Guerino, Guilherme; Martinelli, Suéllen; Choma, Joelma; Leal, Gislaine Camila; Balancieri, Renato; Zaina, Luciana (Journal of the Brazilian Computer Society, 2024)
User eXperience (UX) work within the software industry entails implementing user-centered practices and techniques to acquire and apply insights about users. Given their challenging context characterized by small teams and limited resources, this application can provide software startups with a competitive edge. Despite a growing interest in this field, the perspectives of startup professionals regarding UX work and the challenges they face remain largely unexplored. This paper seeks to explore the perceptions of startup professionals regarding the usefulness of methods and techniques used in UX work, as well as the moments during user interactions with the product or service when they are applied, alongside the challenges inherent in the startup environment. To achieve this, we conducted a survey involving 90 professionals from software startups in Brazil, employing descriptive and inferential statistical methods for data analysis. Our findings reveal that software startup professionals prioritize understanding user needs, capturing feedback, and conducting user tests in their UX work. Interviews are the most commonly utilized method, although usability testing, competitive analysis, and high-fidelity prototyping are also valued across various stages of startup maturity. Furthermore, UX data is primarily collected during user interactions with the product. Additionally, we identified that specific challenges may have a reciprocal relationship with UX attitudes. These findings underscore the perceived value of UX work among software startup professionals, although perspectives vary depending on the startup’s stage.